GIS Cartography Map Figures, 1, 2, 3, 4, 5, 6, 7 for Historical and Imagined GIS Borderlandscapes of the American West: Larry McMurtry?s Lonesome Dove Tetralogy and L.A. Noirscapes, - Travis, Charles (Edinburgh University Press, 2020)
Historical and Imagined GIS Borderlandscapes of the American West: Larry McMurtry’s Lonesome Dove Tetralogy and L.A. Noirscapes, Special Issue University Consortium of Geographic Information Science, International Journal of Humanities and Arts Computing, 14.2 (2020): 134-153 Figure 1. Texan Santa Fe Expedition of 1841–42. Cartographic Inset: A. Ikin, Map of Texas, in ‘Texas, Its History, Typography, Agriculture, Commerce, and General Statistics’ (London: Sherwood, Gilbert and Piper, 1841) The University of Texas at Arlington Libraries Special Collections, Gift of Jenkins Garrett. Figure 2. Ranger, Comanche, Kiowa and Apache, Raidscapes of Texas, 1850s–‘60s. Figure 3. North-South trajectory, and eco-zones of the Lonesome Dove trek, with 1870 Census Population figures. Figure 4. Narrative Locations and Railroads in The Streets of Laredo Inset image: Henry Wellge (attributed) (1850–1917). Laredo, Texas in 1892. Perspective Map of the City of Laredo, Texas. The Gateway to and From Mexico, 1892. Toned lithograph, 19.6Å~33.1 in. Published by American Publishing Co., Milwaukee, Wis. Amon Carter Museum, Fort Worth. Wikicommons. Figure 5. Distinct and Aggregated Noirscapes of Raymond Chandler, WalterMosley, Michael Connelly and Michael Nava. Map phenomenologically illustrates individual and collective location settings described in the selected novels on a city grid of Los Angeles. Figure 6. Hollywood Canteen, Sunset and Cahuenga (Map of Los Angeles) 1942 (David Rumsey Map Collection.) Shadowed Region (Hollywood and LA Civic Center) corresponds to highest density cone areas of aggregated narrative spaces (Hollywood and LA Civic Center labels and arrows added by author.) Figure 7. Kernel Density visualization of aggregated LA Noir narrative spaces, superimposed over Hollywood Canteen Map. Highest density cones areas are located over Hollywood and Civic Center Complex districts of Los Angeles.
International Journal of Humanities and Arts Computing
PUBLISHED
Figure 1. Texan Santa Fe Expedition of 1841?42. Cartographic Inset: A. Ikin, Map of Texas, in ?Texas, Its History, Typography, Agriculture, Commerce, and General Statistics? (London: Sherwood, Gilbert and Piper, 1841) The University of Texas at Arlington Libraries Special Collections, Gift of Jenkins Garrett. Figure 2. Ranger, Comanche, Kiowa and Apache, Raidscapes of Texas, 1850s??60s. Figure 3. North-South trajectory, and eco-zones of the Lonesome Dove trek, with 1870 Census Population figures. Figure 4. Narrative Locations and Railroads in The Streets of Laredo Inset image: Henry Wellge (attributed) (1850?1917). Laredo, Texas in 1892. Perspective Map of the City of Laredo, Texas. The Gateway to and From Mexico, 1892. Toned lithograph, 19.6?~33.1 in. Published by American Publishing Co., Milwaukee, Wis. Amon Carter Museum, Fort Worth. Wikicommons. Figure 5. Distinct and Aggregated Noirscapes of Raymond Chandler, WalterMosley, Michael Connelly and Michael Nava. Map phenomenologically illustratesindividual and collective location settings described in the selected novels on a citygrid of Los Angeles. Figure 6. Hollywood Canteen, Sunset and Cahuenga (Map of Los Angeles) 1942 (David Rumsey Map Collection.) Shadowed Region (Hollywood and LA Civic Center) corresponds to highest density cone areas of aggregated narrative spaces (Hollywood and LA Civic Center labels and arrows added by author.) Figure 7. Kernel Density visualization of aggregated LA Noir narrative spaces, superimposed over Hollywood Canteen Map. Highest density cones areas are located over Hollywood and Civic Center Complex districts of Los Angeles.
Edinburgh, Scotland
Keywords: GIS; American west; Map; Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Identities in Transformation; Manuscript, Book and Print Cultures; environmental anthropology; environmental history